Clinical and Imaging Features of Multiple System Atrophy: Challenges for an Early and Clinically Definitive Diagnosis - Watanabe, Hirohisa (J Mov Disord, 2018)
Multiple system atrophy (MSA) is an adult-onset, progressive neurodegenerative disorder. Patients with MSA show various phenotypes during the course of their illness, including parkinsonism, cerebellar ataxia, autonomic failure, and pyramidal signs. Patients with MSA sometimes present with isolated autonomic failure or motor symptoms/ signs. The median duration from onset to the concomitant appearance of motor and autonomic symptoms is approximately 2 years but can range up to 14 years. As the presence of both motor and autonomic symptoms is essential for the current diagnostic criteria, early diagnosis is difficult when patients present with isolated autonomic failure or motor symptoms/signs. In contrast, patients with MSA may show severe autonomic failure and die before the presentation of motor symptoms/signs, which are currently required for the diagnosis of MSA. Recent studies have also revealed that patients with MSA may show nonsupporting features of MSA such as dementia, hallucinations, and vertical gaze palsy. To establish early diagnostic criteria and clinically definitive categorization for the successful development of disease-modifying therapy or symptomatic interventions for MSA, research should focus on the isolated phase and atypical symptoms to develop specific clinical, imaging, and fluid biomarkers that satisfy the requirements for objectivity, for semi- or quantitative measurements, and for uncomplicated, worldwide availability. Several novel techniques, such as automated compartmentalization of the brain into multiple parcels for the quantification of gray and white matter volumes on an individual basis and the visualization of α-synuclein and other candidate serum and cerebrospinal fluid biomarkers, may be promising for the early and clinically definitive diagnosis of MSA.